Point Estimate Method in Risk Analysis for Tunnel Support System Selection: A Case Study in Taloun Road Tunnel - Sheikhi, H.; Sharifzadeh, Mostafa; Pazoki, A. (n/a, 2008)
Rock mass has generally inhomogeneous nature and required data to design underground structures are inadequate. These data are mainly obtained from site investigations and laboratory tests. So, out put uncertainties during construction process in the rock mass are inevitable. In this paper, a new approach to design primary support patterns based on risk analysis was proposed. With regard to uncertainty in friction angle, rock mass compressive strength and deformation modulus, this approach applies point estimate technique to determination of uncertainty of tunnel stability. The tunnel support pattern was quantified by considering risk analysis, construction costs and tunnel collapse resulted costs. The developed approach was investigated in Taloun road tunnel. Eighteen various support patterns were considered and finally the pattern with the lowest risk level among all of them was proposed. The analysis results show that P9 support pattern consisting of 25 mm diameter, 3.6 m long and 2*2 m grid rock bolts come with 15 cm thick shotcrete reinforced with wire mesh had the lowest risk level in section under study and consequently was proposed as the best support system.